1946
DOI: 10.1111/j.1476-5381.1946.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

The Variation in the Toxicity of Phosgene for Small Animals With the Duration of Exposure

Abstract: In so far as the toxic effects of a lethal inhalant depend upon the amount of material absorbed these effects must depend upon the dosage (Ct) to which animals are exposed, where C=the concentration of the gas in mg. per cubic metre and t =the time of exposure in minutes. It must also depend upon the rate of inhalation and the efficiency of absorption of the gas in the respiratory tract. The present experiments show quantitatively how the median lethal dose of phosgene expressed as the L(Ct)50 varies with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Prior to the London smog incident, animal toxicological studies of air pollution had distinctively military or workplace themes. Studies focused on gases like phosgene with endpoints of lethality or lung pathology (Boyland et al, 1946) or analogous studies with particulate inhalants found in industrial settings, like mining (Ray et al, 1951). However, the 1950's post-London Smog saw the emergence of toxicological studies focusing on the industrial air pollution as encountered by the public.…”
Section: Early Toxicology and Its Impact On Public Sentiment Toward Amentioning
confidence: 99%
“…Prior to the London smog incident, animal toxicological studies of air pollution had distinctively military or workplace themes. Studies focused on gases like phosgene with endpoints of lethality or lung pathology (Boyland et al, 1946) or analogous studies with particulate inhalants found in industrial settings, like mining (Ray et al, 1951). However, the 1950's post-London Smog saw the emergence of toxicological studies focusing on the industrial air pollution as encountered by the public.…”
Section: Early Toxicology and Its Impact On Public Sentiment Toward Amentioning
confidence: 99%